2014
DOI: 10.5897/ijel2013.0521
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the washback effect of the Pakistani Intermediate English Examination

Abstract: The impact of a test on teaching and learning is commonly referred to as the washback effect. This study investigated the nature and scope of the washback effect from the Intermediate English examination on teachers and students of a public sector college in Pakistan. The research relied on qualitative approach utilizing interviews to collect data from six teachers and six students. The data was analysed using open-coding. The results revealed that there seems to be a strong negative washback from the examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The findings of Safa and Jafari (2016) revealed that the final exam adversely affected English as a Foreign Language (EFL) teachers' teaching methodology and promote item-teaching practices as teachers taught according to the test's content and format. Asma et al (2014) shared a similar view after examining the washback effects of the Pakistan intermediate English examination. Phelps (2017) reported the same and concluded that drilling students on the actual test format does not promote learning but reduces it, because it diverts the attention of the class from the subject matter instruction and consumes the time meant for instructional delivery.…”
Section: Curriculum Versus Item-teaching On Students Learningmentioning
confidence: 75%
“…The findings of Safa and Jafari (2016) revealed that the final exam adversely affected English as a Foreign Language (EFL) teachers' teaching methodology and promote item-teaching practices as teachers taught according to the test's content and format. Asma et al (2014) shared a similar view after examining the washback effects of the Pakistan intermediate English examination. Phelps (2017) reported the same and concluded that drilling students on the actual test format does not promote learning but reduces it, because it diverts the attention of the class from the subject matter instruction and consumes the time meant for instructional delivery.…”
Section: Curriculum Versus Item-teaching On Students Learningmentioning
confidence: 75%
“…They advised the students to revise previous exam papers as the "same questions are repeated after every few years which makes the task easy but effect the learning badly" (p. 187). In exploring the washback effect of HSC on teachers and students, Aftab, Qureshi, and William (2014), additionally found out that the examination did not allow the communicative language teaching since it did not test listening and speaking skills. Moreover, its multiple choice-based question pattern and negligence towards assessing critical thinking abilities encouraged poor teaching practices linking classroom activities directly to the questions of the examination.…”
Section: Pakistanmentioning
confidence: 99%
“…Mumtaz's (as cited in Mathew, 2012Mathew, , p. 1663) study on the SSC exam in Pakistan found out that, although the test was flawed and only was preparing the students for the exam, both teachers and students rated the language course good enough to meet their future needs. Aftab et al (2014) noticed how many students in Pakistan did not realize the actual reason for studying English as a subject in the schools; for them, it was one of the papers, which they needed to pass or score well to get the access to higher education or better job. These studies make us aware of the complicated situation in the country where negative washback is a common outcome of testing because of the misaligned nature of the educational system.…”
Section: Pakistanmentioning
confidence: 99%
“…En consecuencia, los docentes deben estar bien capacitados para elegir el modelo de evaluación más adecuado que refleje el desempeño real de los estudiantes. De esta manera, muchos estudios afirman que el desempeño obtenido por los estudiantes a través de los procedimientos de evaluación del idioma inglés suele verse afectado por diferentes aspectos externos a los que se diseña la prueba, uno de estos estudios fue realizado por Aftab et al (2014) en el que demuestran cómo la enseñanza y el aprendizaje se ven influenciados por las prácticas de evaluación. Por otro lado, este tipo de influencia se conoce como Washback.…”
Section: Introductionunclassified